Cleaner production in a shrimp culture farm: a case study - Gomes de Medeiros, Gilson; Normando de Souza Melo, Henio; Marques de Lima, Iran; Lourdes de Souza Melo, Josette; Ralfh Fernandes de Medeiros, Veder (Revista Gestão da Produção Operações e Sistemas, 2009)
The objective of this paper is to present the opportunities for implementing cleaner production (CP) in a shrimp farm. The methodology used was an investigative case study of a production facility located in Northeastern Brazil. The paper addresses general technical aspects of water and energy management and a description of the effluent from this means of production. It discusses quantitative aspects, environmental considerations, and opportunities for CP in the production process phases. Results point to economies in inputs in the form of feed, soil treatments, medications and energy employed in the production process which range from 4% to 27%, underscoring that the small financial gain should be viewed as a source of considerable environmental benefit. The authors conclude in favor of adopting this technique in this segment of agribusiness, highlighting the importance of managing input doses in final effluent quality, as well as adopting a physical-chemical mechanism for remediation of the sodium metabisulphite residue used in the harvesting process. Keywords: Cleaner production, shrimp farming, environmental impacts, Sodium metabisulfite, physical-chemical remediation.